Molecular epidemiology and clinical features of Klebsiella variicola bloodstream infection compared with infection with other Klebsiella pneumoniae species complex strains - Ohno, Tatsuya; Harada, Sohei; Saito, Hiroki; Tanii, Rimi; Komori, Kohji; Kurosawa, Miki; Wakatake, Haruaki; Kanazawa, Minoru; Ohki, Uiri; Minoura, Ayu; Yamada, Mario; Kaneko, Satsuki; et al. (Microbiology spectrum, 2025)
Klebsiella variicola is increasingly recognized as an emerging pathogen commonly found in the environment and human gut. However, its clinical and microbiological characteristics remain poorly understood. This study provides a comprehensive analysis of K. variicola bloodstream infections (BSIs), comparing clinical and genetic features with the closely related K. pneumoniae . We identified significant differences in the prevalence of virulence genes between the two species. Notably, we observed K. variicola causing disseminated liver abscesses, similar to hypervirulent K. pneumoniae strains. These findings have important implications for accurate species identification, informing treatment strategies, and improving patient outcomes in the face of this emerging infectious threat.